How does the COVID-19 pandemic influence educational and psychological health of nursing students in Turkey: What can be done to minimize adverse effects of the pandemic? - Okuyan, Canan Birimoglu; Caglar, Songul; Begen, Mehmet A (Technium Education and Humanities, 2022)
We evaluate the effects of the COVID-19 pandemic on the educational processes, and psychological health of nursing students and provide an overview of the measures that should be taken against minimizing the adverse effects of the pandemic. We find that nursing students experience anxiety and stress during the pandemic due to online education and social isolation. Social media-based health education planning (provided by nursing trainers) and inclusion of online simulation applications to the curriculum can be effective ways to prevent the negative effects of the pandemic on education of nursing students and to protect students' health and ensure that they gain necessary nursing skills as in formal education.